A Comprehensive Systematic Review of The Relationship Between Head Ultrasound Findings and the Risk of Cerebral Palsy in Premature Infants - M. Faza Akroma; Leviani Mulia Primadani (The Indonesian Journal of General Medicine, 2026)
Introduction: Prematurity remains a leading cause of long-term neurodevelopmental disability, with cerebral palsy (CP) being one of the most severe motor outcomes. Cranial ultrasound (cUS) is a primary, non-invasive neuroimaging tool in the neonatal intensive care unit for detecting brain injuries prevalent in preterm infants, such as intraventricular hemorrhage (IVH) and periventricular leukomalacia (PVL). Establishing the strength and consistency of the relationship between specific cUS findings and subsequent CP risk is critical for prognosis, early intervention, and guiding clinical management (Romero-Guzman & López-Muñoz, 2017; O’Shea, 2016). Methods: This systematic review synthesized evidence from 80 studies, including cohort studies, case-control studies, and meta-analyses. The population comprised premature infants (<37 weeks gestation). Studies were included if they involved cUS examination, assessed CP diagnosis with clear criteria, and included follow-up to at least 12 months corrected age. Data extraction focused on premature population characteristics, specific cUS abnormalities, CP assessment methods, quantitative ultrasound-CP associations, and confounding factors (Linsell et al., 2016). Results: The analysis revealed a strong, hierarchical association between cUS abnormalities and CP risk. Cystic PVL showed the strongest association (Odds Ratio [OR] up to 70.9), followed by non-cystic PVL (Relative Risk [RR] 9.27), and severe IVH (Grade III-IV; OR 3.1-3.4). A normal cUS had a high predictive value (99%) for a normal or mildly abnormal MRI. Key risk factors like chorioamnionitis, lower gestational age, and postnatal dexamethasone exposure were significantly linked to both cUS abnormalities and CP. Intervention studies indicated that early treatment for post-hemorrhagic ventricular dilatation (PHVD) and antenatal corticosteroids improved neurodevelopmental outcomes (Gotardo et al., 2019; Hirtz et al., 2015; Cizmeci et al., 2020). Discussion: The heterogeneity in effect estimates across studies is attributable to population differences (e.g., extremely preterm vs. late preterm), timing and technique of cUS assessment, variations in CP outcome definitions, and methodological quality. The evidence confirms that cUS is a valuable prognostic tool, particularly for severe white matter injury and hemorrhage. However, its predictive accuracy is context-dependent, being highest in the most vulnerable infants. The mediating role of cUS-detectable injury in treatment effects (e.g., magnesium sulfate) underscores its importance in understanding pathways to CP (Guillot et al., 2020; Villamor-Martínez et al., 2019). Conclusion: Specific cUS findings, especially cystic PVL and high-grade IVH, are significant predictors of CP risk in preterm infants. Serial cUS screening, particularly at ~1 week and term-equivalent age, is recommended for high-risk infants. Prognostic counseling should consider both the strong reassurance offered by a normal scan and the nuanced interpretation of abnormal findings, acknowledging other contributing risk factors. Future research should prioritize standardized imaging protocols, longitudinal designs with long-term follow-up, and the integration of cUS with advanced imaging modalities for improved prediction.